METHODS OF OPTIMIZING CARGO TRANSPORTATION BY HEAVY-DUTY VEHICLES - Приходько, Всеволод; Вікович, Ігор (SWorldJournal, 2024)
The article discusses methods for optimizing the transportation of heavy goods using large vehicles, which are a key aspect of logistics and transportation infrastructure. Transportation optimization aims to reduce costs, improve efficiency and safety of